Extending Rice et al. (2017): the measurement of social media affordances. Issue 6 (26th April 2022) - Manata, Brian; Spottswood, Erin
ABSTRACT: In a recent issue of Journal of Communication, Rice et al. (2017) offered a measure of social media affordances that has been of decided value to its corpus. Specifically, using a grounded-theory approach, these authors predicted the existence of 11 unique affordances that are manifest within organisational contexts. However, based on exploratory factor analysis, these authors contend that only 6 unique affordances were emergent in their data. Using alternate statistical methods (i.e. confirmatory factor analysis) and newly collected data from two different samples, we show that Rice et al.'s initial 11-factor measurement model provides a good fit to the data. In addition, subsequent analyses show that the measured affordances are largely measuring the same construct (i.e. they are empirically indistinguishable). Additional analyses were also performed to show that both first- and second-order portions of the model remained invariant between different social-media platforms. In the main, these findings suggest a more parsimonious theoretical conceptualisation of the affordances construct as is used in social media contexts, i.e. the possibility of connecting to others online in a social and strategic manner. Moreover, this conceptualisation remains equivalent across different social media platforms.